Reorganización contable en la Empresa “Piladora de Arroz Gallo & Rosillo Cía. Ltda.” del Cantón Macará, periodo del 01 de abril al 30 de junio del 2023 - Castillo Enríquez, Cinthya Mishell (2024)
The present Work of Curricular Integration denominated Accounting reorganization in the Company "Piladora de Arroz Gallo & Rosillo Cía. Ltda." of the Macará Canton, period from April 1 to June 30, 2023, was carried out with the aim of fulfilling the objectives of the investigation, for this purpose a specific analysis is carried out in order to determine the most relevant aspects, to implement solutions to develop the company, designed a plan and manual of accounts which correspond to the operations executed in the company, the initial inventory was prepared, allowing to know the value of its assets with a total of $ 783,721.20, a value of its liabilities with a total of $ 575,769.81 and with respect to its patrimony with a total of $ 207,951.39, then were collected, organized and recorded the operations through the proposed auxiliaries, created based on the needs of the company, these were recorded in the daily book, the system of control of inventories by permanent account was used, based on this information was elaborated the general ledger of each accounting account used in the financial period; subsequently, the trial balance was made, identifying the balances of each account, followed by the worksheet for the preparation of the financial statements, and the respective adjustments for the closure of accounts, the financial statements were prepared, the statement of financial position reflects a total of assets of $1,084,417.46 a total of liabilities of $860,834.49 and total equity of $223,582,97, the statement of results reflects a total income of $873,212.59 and a total outflow of $176,953.83, obtaining a profit of $73,560.39, once the work was prepared, the conclusions were determined which indicate the most relevant aspects that must be taken into account for decision-making within the company.